2020
DOI: 10.1111/pala.12488
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary stasis, ecophenotypy and environmental controls on ammonite morphology in the Late Cretaceous (Maastrichtian) Western Interior Seaway, USA

Abstract: We test for the presence of evolutionary stasis in a species of Late Cretaceous ammonoid cephalopod, Hoploscaphites nicolletii, from the North American Western Interior Seaway. A comprehensive dataset of morphological traits was compiled across the entire spatial and temporal range of this species. These were analysed in conjunction with sedimentologically and geochemically derived palaeoenvironmental conditions hypothesized to apply selective pressures. All changes in shell shape were observed to be ephemeral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 63 publications
3
12
0
Order By: Relevance
“…Morphometric Measurements.-Morphometric parameters were measured on wellpreserved adult specimens and are the same as those described in Witts et al (2020) for the closely related species Hoploscaphites nicolletii (Fig. 3).…”
Section: Methodsmentioning
confidence: 99%
“…Morphometric Measurements.-Morphometric parameters were measured on wellpreserved adult specimens and are the same as those described in Witts et al (2020) for the closely related species Hoploscaphites nicolletii (Fig. 3).…”
Section: Methodsmentioning
confidence: 99%
“…Morphological adaptations suited to an infaunal mode of life are also noted in other groups such as boring bivalves with their asymmetrical, streamlined shells with a tapering posterior (Stanley 1970) and marine gastropods belonging to Strombidae (Savazzi 1991; Everett 2020). Similarly, groups displaying patterns of long-term shape conservatism include the turritellid gastropods (Allmon et al 1990), Cretaceous cyclophorid land snails (Hirano et al 2019), the Cretaceous ammonite species Hoploscaphites nicolletii (Witts et al 2020), the Cretaceous Jacobsoniidae beetles (Yamamoto et al 2017), the Devonian brachiopod genus Tropidoleptus (Isaacson and Perry 1977), and the Nearctic squirrel clades (Zelditch et al 2015). Furthermore, in the case of marine gastropods, previous studies have demonstrated that morphological features are selected to enhance ecological functioning; for instance, a low spire height and low apertural inclination help in making shells gravitationally more stable (Vermeij 1971; Noshita et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Witts et al (2020) examined shell shape in Late Cretaceous ammonites (a group of extinct molluscs with coiled shells, related to squid). Tracing the species Hoploscaphites nicolletii across its entire spatial and temporal range, the authors found no directional trend but variations in shell shape correlated with those of paleoenvironmental proxies.…”
Section: Correlation With Paleoenvironmental Variationmentioning
confidence: 99%